Perfluorooctanoic acid, perfluorooctanesulfonate, and serum lipids in children and adolescents: results from the C8 Health Project - Frisbee, Stephanie J. (2010)
OBJECTIVE: Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS) are man-made compounds with widespread presence in human sera. In previous occupational and adult studies, PFOA and PFOS have been positively associated with serum lipids. Our objective is to interrogate the association between PFOA and PFOS and serum lipids in children. DESIGN: Cross-sectional community-based study. SETTING: Mid-Ohio river valley. PARTICIPANTS: 12,476 children included in the C8 Health Project, resultant from the pre-trial settlement of a class action lawsuit pursuant to PFOA contamination of the drinking water supply. MAIN OUTCOME MEASURES: Serum lipids (total, HDL, and LDL cholesterol, and fasting triglycerides). RESULTS: Mean serum PFOA and PFOS concentrations were 69.2±111.9 ng/mL and 22.7±12.6 ng/mL. In linear regression after adjustment for covariables, PFOA was significantly associated with increased total and LDL cholesterol, and PFOS was significantly associated with increased total, HDL, and LDL cholesterol. In GLM ANCOVA analysis, between the 1(st)—5(th) quintiles of PFOA there was a 4.6 mg/dL and 3.8 mg/dL increase in the adjusted mean of total and LDL cholesterol, and an 8.5 mg/dL and 5.8 mg/dL increase in the adjusted mean for total and LDL cholesterol between the 1(st)—5(th) quintiles of PFOS. Increases were 10 mg/dL for some age- and gender-group strata. Observed effects were non-linear, with larger increases in total and LDL cholesterol occurring the lowest range of particularly PFOA. CONCLUSIONS: While the epidemiologic and cross-sectional nature of the current study limit causal inferences, the consistent observed associations between increasing PFOA and PFOS and elevated total and LDL cholesterol warrant further study.